Experiment with surface subdivision schemes - Sim, Yan Qing (2014)
This project studies the surface subdivision schemes and the possible combination of these subdivisions. The experimentation and evaluation on performances of the Loop, Butterfly, and LoopButterfly subdivisions were carried out to determine the best subdivision techniques that can effectively smooth the object surface.